The effects of melatonin and the antioxidant defence system on apoptosis regulator proteins (Bax and Bcl-2) in experimentally induced varicocele - Onur, R; Semerciöz, A; Orhan, I; Yekeler, H (Springer, 2004)
Our aim was to examine the effects of melatonin on the testicular tissue of adult rats with experimentally-induced left varicocele, and to determine the relationship between melatonin and apoptosis regular proteins in the anti-oxidant defence system. Forty adult male Wistar rats were divided equally into four groups. A sham operation was performed on the rats in group I, and experimental left varicocele was created in groups II, III and IV. Melatonin was administered intraperitoneally at doses of 5 mg/kg and 10 mg/kg to rats in groups III and IV, respectively. An immunohistochemical analysis of the left testicular tissue was performed to evaluate the expression of Bax and Bcl-2, while tissue malondialdehyde (MDA) and antioxidant enzyme activities were assessed in homogenates to determine the role of the oxygen defence system. The immunohistochemical analysis revealed an increased ratio of pro-apoptotic protein Bax in groups II and III, whereas no significant activity was observed in the sham operated rats (P<0.05). Similarly, the tissue MDA level increased and a significantly decreased level of antioxidant enzymes was observed in these groups (P<0.05). Although rats in group IV showed a slightly increased ratio of the pro-apoptotic marker Bax, there was no significant difference between groups I and IV. Similarly, group IV showed decreased levels of MDA and increased levels of anti-oxidant enzyme activity with decreased Bax expression. The close relationship between pro-apoptotic/anti-apoptotic markers, reactive oxygen species and antioxidant agents provided a useful in vivo model for studying the pathophysiology of varicocele and evaluating the role of antioxidants in the prevention testicular damage.
Keywords: varicocele; apoptosis; Bax; Bcl-2; melatonin; reactive oxygen species